High Stability Industrial-Grade Nd: YVO4 Picosecond Laser Amplifier With High Average Output Power - Bai, Zhenao; Zhang, Yakai; Lin, Weiran; Yan, Xiaochao; Fan, Zhongwei (Frontiers in Physics, 2022)
We demonstrate a high-power Nd: YVO4 picosecond laser amplifier that is capable of generating 51.5 W of average output power at a wavelength of 1064 nm, with a repetition rate of 70 MHz and a pulse duration of 8.5 ps. This system encompasses three stages of laser diode end-pumped Nd: YVO4 amplification including two double-pass amplifiers and a single-pass amplifier. Laser output with near-diffraction-limited beam quality (M2 < 1.1) was maintained throughout the entire power scaling range of the laser. The system exhibited very high output power stability with a root-mean-square amplitude fluctuation of less than 0.2% over a period of 15 hours of continuous operation.